Diseño editorial empleando imágenes anaglifas de las principales iglesias de la ciudad de Latacunga, provincia de Cotopaxi - Mena Molina, Jackeline Del Rosario (2017)
The research work dominated “Editorial design using anaglyphic images of the main churches of Latacunga city, Cotopaxi province” is based in the necessity of the diffusion of the main churches that Latacunga city has. The use of materials for the diffusion of the main churches was inquired for the diffusion of the Latacunga city main churches, so it is possible to problematize the current situation, it focuses on the necessity for an innovative editorial design that helps the diffusion of the Latacunga city main churches. Based on the problem identification, the general and specific objective for the problem solution was established, which is based on the editorial design elaboration using anaglyphic images of the Latacunga city main churches. The theoretical scientific-technical reference on three-dimensional design, anaglyph image was proposed for its diffusion as specific objectives….